The Role of a Notary in a Credit Agreement with Mortgage Guarantee at BPR Sinar Mas Pelita Sindanglaut Cirebon - Senusha, Sekar; Adillah, Siti Umi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
In carrying out micro business activities, banks provide several products to assist business actors in running their businesses by providing working capital loans with land ownership guarantees in the form of ownership certificates. The process in the implementation of financing credit by banks involves the role of Notaries. This study discusses the role of notaries in credit agreements with mortgage guarantees at BPR Sinar Mas Pelita, focusing on the legal consequences that arise if there is a discrepancy between the land certificate and the data recorded at the National Land Agency. These problems have the potential to cause disputes, hinder the mortgage registration process, and reduce legal certainty. The purpose of this study is to determine the role of notaries in ensuring the validity of documents and resolving legal problems that arise due to differences in certificate information with data at the National Land Agency. The research method used is empirical juridical with a statutory approach and through interviews with notaries, banks and customers. The research results indicate that notaries play a crucial role as public officials, ensuring that the formal and material requirements of credit agreements are met, including verifying certificates and land data before the deed is signed.